Taxonomy and Phylogeny of Rust Fungi on Hamamelidaceae - Liu, Yun; Cao, Bin; Tian, Chengming; Ono, Yoshitaka; Lin, Weiwei; Liang, Yingmei (Frontiers in Microbiology, 2021)
Hamamelidaceae is composed of woody plant taxa of important economic value; however, reports on diseases affecting these plants are rare. Three kinds of rusts were studied, of which the first one is characterized by catenulate spores in peridiate columnar sori on Sycopsis sinensis, the second one produces two-celled pedicellate teliospores in pulvinate sori on S. sinensis and Corylopsis spp., and the last one produces aeciospores in cup-shaped aecia on Hamamelis spp. Phylogenetic analyses indicated that the three species belong to the same genus in Pucciniaceae. The first fungus is distinct in teliospore morphology, producing one-celled catenulate spores in peridiate columnar sori and molecular phylogeny from species of other genera. Thus, it is described herein as a new genus and species Novopuccinia sycopsis-sinensis in Pucciniaceae. The latter two species were reported as Puccinia corylopsidis and Aecidium hamamelidis, respectively. However, phylogenetic analysis using ITS and 28S genes has revealed that these are closely related to the new genus and species. By combining host, distribution, and evolutionary hypothesis of rust fungi with endocyclic life cycle, these are reclassified as N. corylopsidis and N. hamamelidis. Taxonomic descriptions, illustrations, and a key to rust fungal species occurring in Hamamelidaceae in Asia are provided.